Changes in attitudes of full-time and part-time nursing students in Croatia on nursing during their education - Snježana Čukljek; Vesna Jureša; Sanja Ledinski Fičko; Ana Marija Hošnjak; Martina Smrekar (University of Ostrava, 2019)
Aim: The aim of this study was to determine the attitudes of nursing students towards nursing, and differences in attitudes between students engaged in full-time and part-time nursing study. Design: A three-year longitudinal study was conducted. Methods: A three-year longitudinal study was conducted. The study included full-time and part-time students in their first and final (third) year of nursing study. The students voluntarily completed the Nursing Image Questionnaire (NIQ7) and a questionnaire that included demographic information. Results: The results showed a statistically significant difference between full-time and part-time students in attitudes towards nursing roles and responsibilities, professionalism, and nursing stereotypes in society. An analysis of variance showed that full-time and part-time students did not differ in mean results from the NIQ7 in their first year of study, after which results increased in value for both group of students, increasing somewhat faster for full-time students, with their final results after the third year of study being higher than those of part-time students. Conclusion: Attitudes towards nursing changed in both groups of students (full-time and part-time) during their study programs, but with some differences between the groups.